Bio-ecology of Macaca fascicularis population in Pool Bus area, IPB University (Indonesian Journal of Primatology, 2026)
The long-tailed macaque (Macaca fascicularis Raffles, 1821) belongs to the Cercopithecinae family. Under Regulation of the Minister of Environment and Forestry Number 26/Kpts-II/94 on the Utilization of Long-tailed Macaque (Macaca fascicularis), Southern Pig-tailed Macaque (M. nemestrina), and Asian Arowana (Scleropages formosus), Indonesia captivates and exports M. fascicularis. At IPB University, M. fascicularis occupies the pool bus area as one of its habitats. In this study, we observed a total of 19 individuals: two adult males, five adult females, eight juveniles, and four infants. The age structure alone indicates the potential for further population growth. This population thrives due to the abundance of food resources and fresh water in the pool bus area. As frugivores, M. fascicularis in this area shows a preference for fruit, with eight out of 12 foods being fruits. They consume star fruit (Averrhoa carambola), yellow mombin (Spondias mombin), palm fruit (Elaeis guineensis), corn (Zea mays), banana (Musa sp.), papaya (Carica papaya), jeluak (Microcos tomentosa), and melinjo (Gnetum gnemon). Additionally, we found that they use Parkia timoriana as their sleeping tree.